An in vitro study on the influence of laser-activated irrigation on infiltration and leakage of a dual curing-resin cement as an endodontic sealer - Laurine Marger; Marwa Abdelaziz; Enrico di Bella; Ivo Krejci; Clara Isabel Anton y Otero (Medical Journals Sweden, 2024)
Objectives: The study aims to investigate the effects of laser-activated irrigation on infiltration and microleakage of a dual-curing resin cement applied as a root canal sealer. Methods: Thirty-eight extracted upper molars were attributed to four experimental groups. Roots were mechanically enlarged and disinfected (NaOCl). Control samples (n = 11) were irrigated with conventional needles and three different lasers were used to activate the irrigant in the other groups (n = 9): 2.94 µm Er:YAG laser, 9,300 µm CO2 laser and 808 nm diode laser with a modified black coated laser tip. Final irrigation was performed in each group with ethylenediaminetetraacetic acid (EDTA),  sodium hypochlorite (NaOCl) and sodium chloride (NaCl) activated with lasers and in the control without activation. Dentin tubules were then labeled with a red fluorophore (Rhodamine B) and the root canals were sealed with a dual-curing resin cement (Paracore). The cement fixed the dye on the sealed and infiltrated dentin parts. To remove the Rhodamine not fixed by the cement, roots were then sectioned horizontally and immersed in hydrogen peroxide (H2O2). The empty dentin tubules spaces were then labeled with a green fluorophore (Fluorescein) allowing the visualization of infiltration and microleakage by confocal microscopy. Results: Percentages of infiltration were significantly higher in the middle root third of the control and Er:YAG laser-activated samples compared to CO2 or diode laser groups. Microleakage was present in all experimental groups but significantly less after CO2 laser activation. Conclusion: Laser-activated irrigation impacted resin cement infiltration and microleakage dependent on the applied wavelength. Er:YAG laser activation led to higher values of infiltration and microleakage compared to CO2 and diode lasers.